Youth Radicalism and Security Challenges in Nigeria: The Role of Tijjaniyya Sufi Order in De-radicalization - Jibrin, Hussaini (EBSU Journal of Social Sciences and Humanities, 2021)
There is no doubt that upholding radical or extreme ideologies among the youths is the major factor responsible for the out-break of conflicts that retard economic growth and development, scientific and technological advancement, democratic consolidation as well as political stability in African Continent. For instance, in South Africa, Xenophobia radicalized many youth groups leading to obnoxious killings and hatred against fellow humans. In Kenya, Somalia and other East African countries, the activities of Al-shabab militants threaten economic progress and political stability. In Cameroon and Chad, there are quite a number of radicalized ethnic militias that are very hostile to other ethnic groups and their home governments camouflaging under domination by larger ethnic groups. Similarly, in Liberia and Sierra Leone rebel leaders radicalized thousands of youths in the struggle for control of the nations’ wealth. Nigeria, (the giant of Africa) is not free from these kinds of security challenges in form of youth radicalization. This is because of the presence of different youth groups agitating for resource control, religious extremism and ethnic bigotry. This paper explores the place of Tijjaniyya Brotherhood (a branch of Sufi Sunni Islam) in Nigeria in the de-radicalization activities of their youth members. Thus, it is divided into sub-sections; Introduction, an Overview of the Youth Radicalism and Insecurity in Nigeria, Shi’ah Radicalism, Maitatsine Youth Violence, 1980-1990, Wahhabism, Salafism or Boko Haram Insurgency, Sufism, Tijjaniyya brotherhood and De-radicalization of Youth in Nigeria and Conclusion. The paper adopts both primary and secondary sources of reconstruction of history as published and unpublished works as well as oral interviews were conducted.